Maria Seweryna z Trojackich Pawlikowska jako „Maciuś” na kartach dziennika Maryli Wolskiej z I wojny światowej - Pękalska, Dominika (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The subject of the article is Maryla Wolska’s diary from World War I preserved in the form of a typescript in the National Library of Poland (BN 15273). The document was created between August 15 1914 and April 12, 1918; from June 21, 1915 it was written as a continuous letter to “Maciuś”. This pseudonym referred to Maria Seweryna née Trojacka, the first wife of Michał Pawlikowski, the writer’s a long-time collaborator. The key subject of research is the relation between Wolska and Maria Seweryna – “Maciuś” – preserved in the diary and immersed in the perspective of the author’s World War I experiences. Some of the questions asked in the article are: who is “Maciuś” as a character in Wolska’s text, why “Maciuś” was chosen by the diary’s author as the addressee of her entries and what are the meaning behind the pseudonym given to Trojacka.